DEVELOPMENT OF DEATH PENALTY IN INDONESIA IN HUMAN RIGHTS PERSPECTIVE - Rusito, Rusito; Suwardi, Kaboel (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
Death penalty is essentially a country that takes the life rights of its citizens so that it is contrary to human rights. But it can be justified throughout its application on the grounds of defending other citizens' human rights and positively legally regulating the state towards a tendency of abatement and ultimately elimination altogether. The application of the death penalty can only be carried out against crimes that transcend humanitarian boundaries, threaten the lives of many people, damage the order of life and human civilization, and damage the country's economy. Crimes that can be sentenced to death include: premeditated murder, terrorism, drug trafficking and dealers, and corruption.